Determination of Conditional Extremes of the Functions of Fundamental Symmetric Polynomials: Array - Ioan, Catalin Angelo (Acta Universitatis Danubius. Œconomica, 2022)
The paper demonstrates how the conditional extremes of the functions of fundamental symmetric polynomials, in the case of the positivity of variables, are obtained either by canceling the partial derivatives in relation to the polynomials, or by the equality of all variables.